SCIENCE LITERACY PROFILE OF SCIENCE EDUCATION STUDENTS IN THE CONTEXT OF APPLIED SCIENCE: ANALYSIS OF QUESTION DIMENSION PROPORTIONS AND SCORE ACHIEVEMENTS - Arvidhea Safira Gunawan; Firdha Yusmar; Siti Shofa Assyifa’ul Qulbi Barid; Rekfa Wika Amini; Fauziyatul Iffah; Sri Wahyuni (Universitas Labuhanbatu, 2026)
Purpose- This research was carried out to explain the scientific literacy profile of undergraduate science education students in the context of Applied Science, by examining (1) the proportion of science literacy question dimensions in multiple-choice test instruments, and (2) student achievement scores on each of the question dimensions of scientific literacy.Methodology- This is a descriptive, quantitative study with a one-shot, cross-sectional measurement design. The study group included 115 pre-service science teachers from four parallel (A-D) classes, sampled using total sampling. The test contained 20 multiple-choice questions, which were pre-aligned to four dimensions of scientific literacy, including knowledge, attitudes, context, and competencies, and each of these dimensions was explicitly defined. Procedures included administering the test, scoring dichotomously (correct/incorrect), summarizing achievement by dimension using percent correct, and conducting Classical Test Theory item analysis by calculating percent correct for each item and classifying difficulty.Finding- This study reveals that dimension achievement showed the highest performance in attitudes and moderate performance in knowledge, whereas performance in context and competencies was lower. Item difficulty analysis indicated that most items were easy (p > 0.70), a smaller portion were moderate (0.30–0.70), and none were difficult (p < 0.30), suggesting the instrument is effective for screening foundational mastery but may be less effective at differentiating mid-to-high performance levels.Contribution- This study provides an applied-science, explicit scientific literacy profile for science education students. It delivers practical diagnostic evidence to improve the MCQ instrument by balancing the blueprint, strengthening distractors, and increasing cognitive demand to capture contextual decision-making better